Policy Convergence with or without the European Union: The Interaction of Policy Success, EU Membership and Policy Convergence1. (7th March 2013) - Fink, Simon
Abstract The European Union (EU) is often seen as an institutional environment that facilitates the exchange of information about the effects of policies, and thus promotes convergence towards successful policies. However, current qualitative studies analyze only EU members and cannot dismiss the hypothesis that the relation between policy success and policy convergence is universal and not affected by EU membership. The article analyzes a dyadic data set on privatization policies in the electricity sector to test the interaction hypothesis that joint EU membership not only causes policy convergence, but also increases the effect of policy success on policy convergence. The result is that economic success of privatizations in role‐model countries and joint EU membership both increase the probability of policy convergence. However, there is no interaction between policy success and joint EU membership. Thus, contrary to widely held assumptions, joint EU membership does not amplify learning from each other's policy success.